Clinical Characteristics and Risk Factors for Poor Outcome in Infants Less Than 90 Days of Age With Bacterial Meningitis in the United Kingdom and Ireland. Issue 9 (September 2018) - Okike, Ifeanyichukwu O.; Ladhani, Shamez N.; Johnson, Alan P.; Henderson, Katherine L.; Blackburn, Ruth M.; Muller-Pebody, Berit; Cafferkey, Mary; Anthony, Mark; Ninis, Nelly; Heath, Paul T.
Abstract : Background: To describe the clinical characteristics and risk factors associated with poor outcome in infants <90 days of age with bacterial meningitis. Methods: Prospective, enhanced, national population-based active surveillance for infants <90 days of age with bacterial meningitis in the United Kingdom and Ireland between July 2010 and July 2011. Infants were identified through the British Paediatric Surveillance Unit, laboratory surveillance and meningitis charities. Results: Clinical details was available for 263 of 298 (88%) infants where a bacterium was identified, 184 (70%) were born at term. Fever was reported in 143 (54%), seizures in 73 (28%), bulging fontanelle in 58 (22%), coma in 15 (6%) and neck stiffness in 7 (3%). Twenty-three (9%) died and 56/240 (23%) of the survivors had serious central nervous system complications at discharge. Temperature instability [odds ratio (OR), 2.99; 95% confidence interval (CI): 1.21–7.41], seizures (OR, 7.06; 95% CI: 2.80–17.81), cerebrospinal fluid protein greater than the median concentration (2275 mg/dL; OR, 2.62; 95% CI: 1.13–6.10) and pneumococcal meningitis (OR, 4.83; 95% CI: 1.33–17.58) were independently associated with serious central nervous system complications while prematurity (OR, 5.84; 95% CI: 2.02–16.85), low birthweight (OR, 8.48; 95% CI: 2.60–27.69), coma at presentation (OR, 31.85; 95% CI: 8.46–119.81) and pneumococcal meningitis (OR, 4.62; 95% CI: 1.19–17.91) were independently associated with death. Conclusions: The classic features of meningitis were uncommon. The presentation in young infants is often nonspecific, and only half of cases presented with fever. A number of clinical and laboratory factors were associated with poor outcomes; further research is required to determine how knowledge of these risk factors might improve clinical management and outcomes. Abstract : Supplemental Digital Content is available in the text.